Um olhar dialógico sobre leitura e seus procedimentos nas avaliações do Saeto - Nascimento, Michele Lima (2024)
This dissertation aims to understand how the dialogical assumptions of language (BAKHNTIN, 2015; 2017; 2018; VOLÓCHINOV, 2017; 2019) permeate the evaluations of the System of the Education Evaluation System of the State of Tocantins (SAETO), Applied tostudents of the 5th and 9th grade of elementar school. The specific objectives that guided theseinvestigations are: a) Identify which reading concepts support the SAETO test; b) Understand to what extent the concept of dialogical reading constitutes the evaluation items of the SAETOtest; c) To analyze how the principles od dialogismo permeate the questions that are included in the topic Reading Procedures of the reference matrix of the SAETO test. To achieve the objectives outlined, this research was inserted in the qualitative and interpretive approach (DENZIN; LINCOLN, 2006), from the perspective of Applied Linguistics. This dissertation was based on the conception of dialogical language (VOLÓCHINOV, 2017) and used documentar analyses as a method, because, in these investigations, They use several oficial documents that received analytical treatment. In view of the above, the data indicated that the SAETO is an evaluation system that presents some points of convergence with the perspectiveof dialogical reading, since it provides the reader to form in the midst of various inferential readings, raising ideological valorizations. And some points of disagreement with dialogism, since some questions do not presente the necessary elements of the chronotope of a text for itsinterpretation.